Acquired cutaneous Langerhans cell histiocytosis. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 2-month-old boy was born at term by Cesarean section and received mixed feeding from birth. The family history of atopy was negative. In the second month he presented blood in the stool attributed to intolerance to cow's milk. At the end of the second month appeared punctate asymptomatic lesions started on the neck and then spreaded everywhere. Over the past two months he had grown a little -650 g -. The physical examination (Fig. 1, 2) showed eroded or crusted papules, sometimes purpuric, monomorphic, 1-2 mm in diameter, on the scalp, trunk, retroauricular folds, neck, axillae (Fig. 2) and groin; the trunk lesions did not prefer the middle area. Histological examination of an axillary papule showed (Fig. 3) papillary edema, infiltrate of large histiocytes S-100 +, CD1a+. The child was admitted to the pediatric oncology ward where investigations in blood chemistry, ultrasound, x-ray confirmed the diagnosis of acquired pure cutaneous Langerhans cell histiocytosis. A monthly monitoring of the child was programmed.